PENGETAHUAN DAN SIKAP MASYARAKAT TERHADAP KONSERVASI BURUNG PARUH BENGKOK DI KECAMATAN KEPULAUAN JORONGA - Ardian Hamdani; Zulkifli Ahmad; Chumidach Roini (JURNAL BIOEDUKASI, 2022)
One type of wildlife in Indonesia that is threatened with extinction is the parrot. There are approximately 403 species of parrots in the world, and as many as 81 species are found in Indonesia. One of the areas rich in this bird species is the Maluku Islands, where 32 species of parrots are recorded and 12 of them are endemic to Maluku. Of the 12 bird species, 6 of them are protected. The results showed that the community had known the parrot because 69% had seen it in the forest and 31% had seen it because it was kept. In addition, the knowledge of people who have ever caught and sold parrots has a percentage index value of 23% and 35% or can be categorized as less. Meanwhile, the public knowledge index on the prohibition of catching parrots has an index value of 28% or less agree, 53% implementation of conservation (good enough), conservation participation 47% (high enough), habitat conservation with an index value of 59% (good enough), 24% of the community's knowledge of illegal logging is categorized as poor and the index value of the application of the protection law is 49% (quite agree). The current attitude of the community towards hunting has an index value of 16% or it can be categorized as bad, fishing is also classified as poor or the percentage index is 20%, illegal logging is 26% or the category is not good, and trade bans are in the disagree category (11%), while the lack of logging wild, has a percentage index value of 53% (good enough). The implementation of the Law (village rules) with an index value range of 50% or can be categorized as quite agree, and attitudes towards violators have a percentage index value of 38% or in the less high category, then the implementation of sanctions has an index value of 39% or can be categorized as less good.